Asymmetrical Polymer Vesicles for Drug delivery and Other Applications - Zhao, Yi; Li, Xiaoming; Zhao, Xiaotian; Yang, Yunqi; Li, Hui; Zhou, Xinbo; Yuan, Weien (Frontiers in Pharmacology, 2017)
Scientists have been attracted by polymersomes as versatile drug delivery systems since the last two decades. Polymersomes have the potential to be versatile drug delivery systems because of their tunable membrane formulations, stabilities in vivo, various physicochemical properties, controlled release mechanisms, targeting abilities and capacities to encapsulate a wide range of drugs and other molecules. Asymmetrical polymersomes are nano- to micro-sized polymeric capsules with asymmetrical membranes, which means, they have different outer and inner coronas so that they can exhibit better endocytosis rate and endosomal escape ability than other polymeric systems with symmetrical membranes. Hence, asymmetrical polymersomes are highly promising as self-assembled nano-delivery systems in the future for in vivo therapeutics delivery and diagnostic imaging applications. In this review, we prepared a summary about recent research progresses of asymmetrical polymersomes in the following aspects: synthesis, preparation, applications in drug delivery and others.